Phytochemical and pharmacological evaluation of ethanolic extract of Lepisanthes rubiginosa L. leaves - Hasan, Md. Mahedi (BMC Complement Altern Med, 2017)
BACKGROUND: The current study was conducted to evaluate the antioxidant, analgesic, antihyperglycemic, neuropharmacological and antidiarrheal activities of ethanolic extract of Lepisanthes rubiginosa L. leaves in different experimental models. METHODS: Quantitative and qualitative analysis were done by TLC (thin layer chromatography) and DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging assay. Analgesic, antihyperglycemic and antidiarrheal activities were evaluated using acetic acid induced writhing in mice, oral glucose tolerance test and castor oil induced diarrhea, respectively. Neuropharmacological activity was investigated in mice using both Open Field and Hole Board methods. RESULTS: TLC analysis indicated the presence of antioxidant compounds in the extract we used. The extract showed IC(50) value was 31.62 μg/mL whereas the standard ascorbic acid showed 12.02 μg/mL. In acetic acid induced writhing assay, the extract showed 46.07% and 58.43% writhing inhibition at the doses of 250 mg/kg and 500 mg/kg body weight, respectively whereas standard diclofenac-Na (25 mg/kg) showed 86.52% writhing inhibition. The plant extract showed significant (p < 0.05) antihyperglycemic activity on mice as compared to control groups. In neuropharmacological activity assay the experimental animal showed a noticeable decrease in locomotion by showing a decrease in number of square crossed and head dipping at both doses (250 mg/kg & 500 mg/kg). In antidiarrheal activity test, the plant extract at the doses of 250 mg/kg and 500 mg/kg showed percent inhibition of defecation 57.89 and 77.19 respectively, whereas standard loperamide (3 mg/kg) showed percent inhibition of defecation 88.59. CONCLUSION: The results demonstrated that the extract has potential antioxidant, analgesic, antihyperglycemic, neuropharmacological and antidiarrheal activity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12906-017-2010-y) contains supplementary material, which is available to authorized users.